SILICON IN ROW AND NITROGEN IN TOPDRESSING FERTILIZATION ON RICE UNDER DRY LAND AND SPRINKLER IRRIGATION CONDITIONS - Camarin Alvarez Artigiani, Angela Cristina [UNESP]; Costa Crusciol, Carlos Alexandre [UNESP]; Nascente, Adriano Stephan; Arf, Orivaldo [UNESP]; Felix Alvarez, Rita de Cassia (Univ Federal Uberlandia, 2014)
The objective of this work was to evaluate the effects of silicon application adjusted with nitrogen fertilization via top-dressing on grain productivity, the silicon contents of the soil, in the plant tissue and nitrogen contents in dry and irrigated conditions. The experimental outlining was from designed blocks with subdivided parcels and four repetitions. The treatments consisted of culture system (dry and irrigated) and the under parcels by the combination of silicon (0 and 100 kg ha(-1)), in magnesium and calcium silicate form (with 23% of SiO2), and four doses of N (urea) via top-dressing (0, 30, 60 and 90 kg ha(-1)). Silicon application at sowing furrow was a viable technique because it provided significant increase in the content of this element in the root growth of rice. The application of silicon in the sowing furrow did not change the content of the element nor the nitrogen nutrition in rice plants. The nitrogen application reduced the silicon content and increased nitrogen nutrition in rice plants. Silicon application at sowing furrow provided no increase in rice grain yield. When there was no water limitation to nitrogen fertilization enhanced linearly on rice grain yield, whereas under water stress the effect of nitrogen fertilization was limited.
Keywords: Oryza sativa L.; Silicate; Cultivation systems; Plant nutrition